2022
DOI: 10.3390/ma15010360
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Pitting-Corrosion Resistance of Ultrafine-Grained 7475 Al Alloy by Aging

Abstract: The effect of aging on the resistance to pitting corrosion of ultrafine-grained 7475 aluminium (Al) alloy processed by hydrostatic extrusion (HE) is studied. Differences in the microstructure were investigated using secondary electron (SEM) and transmission electron microscopy (TEM). Corrosion tests were performed in 0.1 M NaCl, and characterization of corroded surface was performed. The results of this work show that the pitting susceptibility of ultra-fine grained 7475Al is related to the distribution of MgZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…For pure Al, adiabatic heating during hydrostatic extrusion with a strain of ε = 1.4 should be approximately 120-130 • C, and may influence or initiate the precipitation process in the case of age-hardenable alloys [31]. For AA 7475, the hydrostatic extrusion process changed the precipitation kinetics and phase stability induced by the grain boundaries [32]. Precipitation occurs along fast diffusion paths, such as grain boundaries and dislocations.…”
Section: Microstructural Evolution Through Hydrostatic Extrusion With...mentioning
confidence: 99%
“…For pure Al, adiabatic heating during hydrostatic extrusion with a strain of ε = 1.4 should be approximately 120-130 • C, and may influence or initiate the precipitation process in the case of age-hardenable alloys [31]. For AA 7475, the hydrostatic extrusion process changed the precipitation kinetics and phase stability induced by the grain boundaries [32]. Precipitation occurs along fast diffusion paths, such as grain boundaries and dislocations.…”
Section: Microstructural Evolution Through Hydrostatic Extrusion With...mentioning
confidence: 99%
“…The results further revealed that appropriate heat treatment following HE can improve mechanical strength [6] due to the combination of grain boundaries and precipitation strengthening. Moreover, the resistance to pitting corrosion of AA 7475 samples that underwent HE was improved following aging [19]. Such an improvement is caused by the coarsening of stable intergranular MgZn 2 precipitates and the formation of metastable MgZn 2 in grain interiors during aging.…”
Section: Introductionmentioning
confidence: 99%
“…Since aluminum (Al) alloys have many advantages, such as low density, good strong plasticity, corrosion resistance, and good electrical and thermal conductivity, they have a wide application prospect in the fields of rail transit, ship, and aerospace [1][2][3][4][5]. At room temperature, their mechanical properties can well meet the standard of material selection for light-weight and high-strength structural materials [6].…”
Section: Introductionmentioning
confidence: 99%